Comparing human respiratory adverse effects after acute exposure to particulate matter in conventional and particle-reduced swine building environments. Issue 10 (4th July 2016) - Hedelin, Anna S; Sundblad, Britt-Marie; Sahlander, Karin; Wilkinson, Kai; Seisenbaeva, Gulaim; Kessler, Vadim; Larsson, Kjell; Palmberg, Lena
Abstract : Objectives: To evaluate innate immunity responses, lung function and symptoms in volunteers acutely exposed to organic dust in swine buildings after installing particle separators aimed to reduce particulate matter exposure. Methods: 11 healthy participants were exposed in 2 different facilities, with and without installed particle separators, in a cross-over design including 2–3 weeks wash-out between the 2 exposures. Size, distribution and composition of particulate matter and endotoxins in the air were measured. Lung function (spirometry), bronchial responsiveness, symptoms questionnaire and markers of innate immunity in blood and nasal lavage were measured before and after the 3-hour exposures. Results: The number of particles, in particular fine particles sized 0.3–0.5 µm, was reduced in the particle-separated swine building environment (PSE) compared with that in the conventional building (CE). In the PSE, headache (p=0.03) and increased body temperature (p=0.016) were less pronounced than in the CE. The expression of toll-like receptors (TLR)2 and TLR4 on blood monocytes significantly increased (p=0.016 and 0.017, respectively) while cluster of differentiation (CD)14 on neutrophils decreased (p=0.05) after exposure in the CE, yet with no difference between the 2 exposures. Compared with the conventional environment, exposure to the PSE yielded lower interleukin (IL)-6 (p=0.02) and IL-8 (p=0.04) levels in the upper respiratory tract, as assessed by nasal lavage. Conclusions: Particulate matter and organic dust in the swine building were reduced after installing particle separators, which, in naïve never exposed volunteers, in turn reduced adverse health effects caused by acute exposure in swine buildings compared with exposure to the conventional swine building environment.